التنوع الثقافي في الجزائر : التعايش مع الإختلاف: Cultural diversity in Algeria: coexistence with difference - سعد الشاكر ابراهيم (Maalim, 2022)
This study aims to identify the reality of cultural diversity in Algeria. The history of Algeria's cultural structure has shown that the cultural and civilizational diversity there is authentic. However, French colonialism took the initiative to erase the Arab-Islamic identity by marginalizing the Arabic language and reviving the Amazigh question for the benefit of the hegemony of the French language and its culture, and this presented to the eve of the independence of Algeria a cultural problem, which has intensified with the politicization of cultural trends in Algeria, cultural differences have appeared and despite the difference, there is coexistence between these trends within the framework of the national unity.